Basic magnesium sulfate whisker reinforced polylactide compound as well as preparation method and application thereof

By introducing basic magnesium sulfate whiskers into polylactide, the problem of acidic by-product generation during the degradation of polylactide in vivo is solved, and the strength, rigidity and degradation speed of the material are improved, and it is suitable for soft tissue repair.

CN119405910AActive Publication Date: 2025-02-11ZHONG DING KAI RUI TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411605802.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-11
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Polylactide produces acidic by-products during the degradation process in vivo, leading to an inflammatory response, and its flexural modulus is insufficient and its degradation cycle is too long, making it difficult to meet the needs of soft tissue repair.

Method used

Basic magnesium sulfate whiskers are introduced as the reinforcement component of polylactide, and polylactide composites with improved strength, rigidity and degradation speed are prepared by copolymerization technology.

Benefits of technology

The bending modulus and degradation speed of polylactide are improved, the generation of acidic by-products is reduced, and the biocompatibility of the material is enhanced and the ability to promote tissue regeneration is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the field of biodegradable material modification, and particularly relates to a basic magnesium sulfate whisker reinforced polylactide compound as well as a preparation method and application thereof. The basic magnesium sulfate whisker reinforced polylactide compound disclosed by the invention is prepared from the following components in percentage by mass: 80 to 97.5 percent of saccharic acid lactone modified polylactide and 2.5 to 20 percent of basic magnesium sulfate whisker. The basic magnesium sulfate whisker reinforced polylactide compound provided by the invention has relatively high modulus and rigidity, the strength has early vacancy support, ligation and fixation functions, the compound is gradually degraded and is absorbed and replaced by tissues, and degraded components can provide various organic components for promoting tissue regeneration, so that the regeneration and reconstruction functions of the tissues are improved; the degradation speed can be controlled according to composition and is matched with tissue regeneration and reconstruction. In the using process, operation infection caused by bacterial infection and inflammation such as red and swollen, seepage and the like can be reduced, and wide application in the aspects of operation ligation fixation, defect repair, short-term fixation, isolation and the like can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biodegradable material modification, and particularly relates to a polylactide composite reinforced with basic magnesium sulfate whiskers, and a preparation method and application thereof. Background Art

[0002] Human soft tissues need to be repaired and restored due to surgery and trauma. Unlike hard tissues such as bone tissue, the repair cycle of soft tissues such as muscles and blood vessels is shorter than that of hard tissues. Non-degradable and difficult-to-degrade materials are not suitable as isolation and fixation materials for their wounds. Materials with high initial strength and stiffness and complete degradation in a short period of time are needed as various ligature fixation materials. Currently, polylactic acid (PLA), poly 1,4-dioxanone (PPDO) and polyamino acids are the main materials in this regard.

[0003] Polylactide, also known as polylactic acid (PLA), is a polymer obtained by polymerization of lactic acid or lactide as the main raw material. The raw material source is sufficient and renewable. The production process of polylactide is pollution-free, and the product can be biodegraded and circulated in nature, so it is an ideal green polymer material. It is currently widely used in clothing, packaging, construction, medicine and medical equipment. For example, anti-adhesion membrane is an isolation and bridging repair material widely used in clinical practice for polylactide. The polylactide anti-adhesion membrane effectively isolates the surgical wound from the adjacent organ tissues to avoid adverse adhesion between the wound and the surrounding tissues, so as to isolate the surgical wound and strengthen the weak parts of the soft tissue. It is used in surgical operations such as intervertebral disc herniation, gallstones, appendicitis, uterine tumors, etc. to prevent postoperative adhesion. The lactic acid component of polylactide has the same structure and chemical composition as the lactic acid produced in the human body. Its degradation metabolism is the same as the lactic acid metabolism pathway in the human body. The final metabolite is water dioxide, which has no accumulation in the body and is harmless to the human body. However, polylactide produces acidic byproducts during its degradation in the body, resulting in a low pH at the implant site, which in turn triggers an inflammatory response. The acidity in turn accelerates the degradation of lactic acid, making the surrounding environment continuously acidic, affecting tissue healing and growth recovery. This is one of the problems that needs to be solved urgently.

[0004] On the other hand, polylactide has a tensile strength of 20-60MPa and an elongation at break of 4-10%. Although its elastic modulus can reach 3000-4000MPa, its bending modulus is only 100-150MPa. Its degradation cycle also varies according to its structure. For example, the degradation cycle of DL-polylactide is 12-16 months; the degradation cycle of L-polylactide is more than 24 months. As a medical material, the performance of polylactide has the following problems:

[0005] (1) If used as a fixed material, its bending modulus needs to be improved, and its rigidity and resistance to bending deformation under stress conditions need to be enhanced.

[0006] (2) The degradation cycle is too long. 12-24 months does not match the repair and recovery cycle of soft and hard tissues. It is necessary to increase the degradation rate and shorten the degradation cycle.

[0007] (3) The elongation at break of polylactide is only 4-10%, and its toughness is poor and needs to be improved.

[0008] Especially as a support body, such as temporary support and fixation of bone injuries, ligation of blood vessels and bile ducts, etc., higher rigidity is required, and after completing the support, fixation and ligation functions, it needs to be able to degrade in a relatively short period of time, such as complete degradation in 4 to 12 weeks, so that tissue function can be fully restored.

[0009] Since polylactide is a fully degradable material, ordinary glass fiber, carbon fiber, quartz fiber and basalt fiber are not suitable as reinforcing materials because they cannot be degraded. Although natural fibers such as ramie fiber have high strength, their rigidity is not enough and they are not suitable as reinforcing materials for polylactide. Inorganic fibers or whiskers are still needed to reinforce polylactide. Considering that medical polylactide will interact with tissues, the reinforcing materials used must be non-toxic and safe. Inorganic whiskers used as drugs are preferred. Inorganic whiskers have the reinforcing function of fibers and have high rigidity and bending modulus. When used for ligation and fixation, the reinforcing whiskers will gradually degrade and be absorbed and metabolized during the gradual degradation of polylactide. Therefore, when choosing inorganic whiskers, its composition should be considered first. Metal ions should be selected from the components of human tissues, such as sodium, potassium, calcium, magnesium, etc., or a small amount of trace elements, such as strontium, zinc, etc. The inorganic components of whiskers can be metabolized smoothly and are safe and non-toxic, such as sulfate, chloride, phosphate, etc.

[0010] Therefore, there is an unmet need in the art for inorganic whisker reinforced polylactide materials suitable for medical applications. Summary of the invention

[0011] Taking the above factors into consideration, the present invention selects basic magnesium sulfate whiskers with magnesium sulfate and magnesium hydroxide as the main components, which are commonly used clinical therapeutic drugs, as the reinforcing component of polylactide. The whiskers can be metabolized in the body, have good compatibility with tissues, and provide beneficial effects and functions for tissue regeneration and functional recovery. Moreover, as a reinforcing component, it has a small amount, can enhance the rigidity and strength of polylactide, and can maintain other properties of polylactide unchanged. Properties, uses and production process of basic magnesium sulfate whiskers Chemical properties Appearance: white powder, relative density 2.3, apparent density <0.1g / cm 3 , specific surface area <10m 2 / g, oil absorption 500m1 / 100g, fiber diameter <1μm, fiber length 10-100μm, aspect ratio 50-100, crystal shape is needle-shaped or fibrous, with excellent electrical properties, and affinity to water and organic solvents. Because it contains crystal water, the use temperature is lower than other whiskers, mostly below 250°C. At the same time, due to the presence of crystal water, the whiskers have excellent flame retardancy. Uses have excellent reinforcement effect on plastics, and the effect of improving the bending elastic modulus is better than that of glass fiber and talc. In addition, as a medical material, in addition to the reinforcement effect, the biological safety of basic magnesium sulfate whiskers must also be considered, so the present invention also prepares medical basic magnesium sulfate whiskers.

[0012] Specifically, in one aspect, the present invention provides a polylactide composite reinforced with basic magnesium sulfate whiskers, which comprises the following components in weight fractions: 80-97.5% of polylactide modified with sulphonolactone and 2.5-20% of basic magnesium sulfate whiskers.

[0013] Furthermore, the polylactide modified by saccharolactone is copolymerized by lactide and saccharolactone, wherein the content of lactide is 80-99 mol % and the content of saccharolactone is 1-20 mol %.

[0014] Furthermore, the sugar acid lactone includes at least one of glucono-δ-lactone, glucono-γ-lactone, D-mannose-1,4-lactone and L-mannose-1,4-lactone.

[0015] Furthermore, the basic magnesium sulfate whisker is at least one of type 152 and type 150 basic magnesium sulfate whiskers.

[0016] In another aspect, the present invention provides a method for preparing a polylactide composite reinforced with magnesium sulfate whiskers as described herein, comprising the following steps:

[0017] (1) Preparation of basic magnesium sulfate whiskers: mixing an aqueous solution of a weakly alkaline organic magnesium salt with an aqueous solution of magnesium sulfate, then adding an aqueous solution of a basic amino acid under stirring, subjecting the uniformly mixed solution to a hydrothermal reaction, filtering and collecting the obtained reaction product, and washing and drying to obtain basic magnesium sulfate whiskers;

[0018] (2) Preparation of polylactide modified with saccharo lactone: adding lactide, saccharo lactone and a catalyst into a reaction kettle under the protection of nitrogen or an inert gas, and reacting at 120-180° C. for 6-50 hours to obtain polylactide modified with saccharo lactone;

[0019] (3) Preparation of a polylactide composite reinforced with magnesium sulfate whiskers: The magnesium sulfate whiskers prepared in step (1) and the polylactide modified with succinolactone prepared in step (2) are melt-extruded together in a desired mass ratio to obtain a polylactide composite reinforced with magnesium sulfate whiskers.

[0020] Furthermore, the molar ratio of the weakly alkaline organic magnesium salt to magnesium sulfate is 1.0:3.0-6.0.

[0021] Furthermore, the molar ratio of the basic amino acid to magnesium sulfate is 1.0:1.0-2.0.

[0022] Furthermore, the organic magnesium salt with weak alkalinity includes at least one of magnesium acetate, magnesium propionate and magnesium butyrate.

[0023] Furthermore, the basic amino acid includes at least one of lysine, histidine and arginine.

[0024] Furthermore, the hydrothermal reaction is carried out under the conditions of 0.4-1.0 mPa and 140-200°C.

[0025] Furthermore, the basic magnesium sulfate whisker is 152 type basic magnesium sulfate whisker.

[0026] Furthermore, the 152 type basic magnesium sulfate whisker is dried at 240-250° C. for 2-10 hours to obtain the 150 type basic magnesium sulfate whisker.

[0027] Furthermore, the catalyst comprises amino acid zinc and / or tin and titanate.

[0028] Furthermore, the amino acid in the amino acid zinc and / or tin includes at least one of phenylalanine, arginine, lysine and histidine.

[0029] Furthermore, the amino acid in the amino acid zinc and / or tin is preferably phenylalanine.

[0030] Furthermore, the amino acid in the amino acid zinc and / or tin is a combination of phenylalanine and another amino acid.

[0031] Furthermore, the amino acid zinc and / or tin is prepared as follows: amino acid zinc or tin complex is prepared using amino acid and zinc salt or tin salt as raw materials.

[0032] Furthermore, the zinc salt is zinc chloride or zinc sulfate, and the tin salt is stannous chloride.

[0033] Furthermore, the amino acid zinc and / or tin is prepared as follows: under the protection of nitrogen or inert gas, the amino acid is reacted with an inorganic guanidine salt in a solvent at 50-80° C. to generate an organic guanidine salt of phenylalanine, and then a water and / or alcohol solution of a zinc salt and / or tin salt is added, and the reaction is carried out at 50-80° C. for 3-8 hours to obtain a zinc and / or tin complex of the amino acid.

[0034] Furthermore, the ratio of the total amount of amino acids to the solvent is 1 (mol): 1-2 (L).

[0035] Furthermore, the molar ratio of the amino acid to the inorganic guanidine salt is 1:0.5-1.2.

[0036] Furthermore, the molar ratio of the amino acid to the zinc salt and / or tin salt is 2:1.

[0037] Furthermore, the solvent is at least one of water, methanol, ethanol, tetrahydrofuran and dioxane.

[0038] Furthermore, the inorganic guanidine salt is guanidine carbonate.

[0039] Furthermore, the method further comprises filtering, collecting, washing and drying the obtained zinc and / or tin complex of amino acid.

[0040] Furthermore, the titanate includes at least one of tetrabutyl titanate and tetrabutyl zirconate.

[0041] Furthermore, the step (2) is carried out in an anhydrous and oxygen-free environment.

[0042] Furthermore, before the heating reaction in step (2), the reaction kettle is evacuated.

[0043] Furthermore, the reaction in step (2) is preferably carried out at 130-140° C., and the reaction time is preferably 16-32 hours.

[0044] Further, the reaction comprises reacting at 120-150° C. for 2-4 hours, and then heating to 130-160° C. for 5-15 hours.

[0045] Furthermore, step (2) further comprises adding a non-protonic solvent to the reactor to dissolve the harvested aminolactam and lactide polymer modified with saccharide lactone, and then precipitating and washing the polymer with a polar solvent and drying it.

[0046] Furthermore, in step (3), the melt extrusion is carried out under the protection of nitrogen or inert gas, and the discharge port of the melt extrusion is protected by nitrogen or dry ice to prevent the polylactide composite reinforced with basic magnesium sulfate whiskers from being oxidized by air or absorbing water.

[0047] In other aspects, the present invention also provides the use of the polylactide composite reinforced with magnesium sulfate whiskers as described herein or prepared by the preparation method described herein in medical treatment.

[0048] Furthermore, the application includes application in soft tissue repair.

[0049] Beneficial effects of the present invention:

[0050] The present invention introduces basic magnesium sulfate whiskers to enhance the strength and rigidity of polylactide, and weaken the acidity of polylactide, and can avoid the stimulation of degradation acid products on tissues, so that polylactide can be used for ligation and other fixation; the introduction of saccharolactone units increases the polarity and degradation rate of polylactide, and can adapt to the tissue repair cycle; titanate and zinc phenylalanine catalysts are used to replace stannous octoate catalysts, and the toxicity of tin is avoided. The basic magnesium sulfate whisker reinforced polylactide composite provided by the present invention has high modulus and rigidity, strength, early vacancy support, ligation and fixation functions, and is gradually degraded and absorbed by tissues. The degradation components can provide a variety of organic components that promote tissue regeneration, and improve the regeneration and reconstruction functions of tissues; its degradation rate can be controlled according to the composition and matched with tissue regeneration and reconstruction. During use, it can reduce surgical infections caused by bacterial infection and inflammation such as redness, swelling, exudation, etc., and can be widely used in surgical ligation fixation, defect repair, short-term fixation and isolation. DETAILED DESCRIPTION

[0051] The present invention implements the preparation and application of the polylactide composite reinforced with basic magnesium sulfate whiskers through the following specific technical route.

[0052] The schematic composition formula of the polylactide composite reinforced with basic magnesium sulfate whiskers of the present invention is:

[0053]

[0054] In Formula I, m 1 、m 2 is the mass fraction of basic magnesium sulfate whisker and polylactide, m 1 +m 2 =100,m 1 ≤20. That is, in the composition of the composite, the content of basic magnesium sulfate whiskers is not higher than 20wt%, which can adjust the acidity, strength and rigidity of the composite, and keep the basic properties of polylactide unchanged. n is the degree of polymerization of polylactide, that is, the number of repeating units contained in a polylactide molecule, n≥1000, that is, the molecular weight (weight average) of polylactide is at least greater than 150,000. x, y, z are Mg(OH) 2 MgSO 4 and H 2O molar ratio. Now found are 138, 165, 435, 115, 152, 153, 157, 158, 150, 212 and 213 and 311 types (the first, second and third digits in the above-mentioned types represent the values ​​of x, y and z respectively), etc., among which 152 type basic magnesium sulfate whisker has the characteristics of high strength, high rigidity, high elastic modulus and low density, and has mechanical properties such as flame retardant, heat resistance and wear resistance, and is the most widely studied one. In the present invention, 152 type basic magnesium sulfate whisker is mainly used as the reinforcing whisker of the polylactide composite reinforced with basic magnesium sulfate whisker, that is, x=1, y=5, z=2; 150 type is used as a supplement, that is, x=1, y=5, z=0.

[0055] At present, the main methods for preparing basic magnesium sulfate whiskers are: 4 and Mg(OH) 2 As raw material, the whiskers were prepared by hydrothermal synthesis, but the conversion rate of this method was low. This is because Mg(OH) 2 Slightly soluble in water, affecting the reaction rate; MgSO 4 and MgO as raw materials, and the whiskers were prepared by hydrothermal synthesis, but the reaction process of this method is more complicated; some researchers also use MgSO 4 and NaOH as raw materials to prepare 152 type basic magnesium sulfate whiskers, but the preparation process requires the addition of seed crystals, resulting in a lower purity of the product.

[0056] The present invention adopts a hydrothermal method of hydrolyzing magnesium sulfate to prepare medical-grade basic magnesium sulfate whiskers. Instead of using basic magnesium compounds that are difficult to dissolve in water, such as magnesium hydroxide and magnesium oxide, organic magnesium salts with weak alkalinity, such as magnesium acetate [(pH value 7.95 (1mM solution); 8.23 ​​(10mM solution); 8.41 (100mM solution); 8.78 (1000mM solution)], magnesium propionate and magnesium butyrate, etc. are used. Sodium hydroxide, potassium hydroxide, lithium hydroxide, etc. are not used to adjust the pH, and amines such as ammonia water and triethylamine are not used to adjust the pH. The present invention adopts alkaline amino acids to adjust the pH, thereby preparing ultrapure basic magnesium sulfate whiskers with less metal ion impurities and no ammonia residue. The specific implementation scheme is: magnesium sulfate is prepared into a 0.5-2.0M solution using deionized water, magnesium acetate (magnesium propionate or magnesium butyrate) is prepared into a 0.5-2.0M solution, and the alkaline amino acid is prepared into a 0.5-2.0M solution. A 0.5-2.0M solution is made; further, a magnesium acetate (magnesium propionate or magnesium butyrate) solution is added to a magnesium sulfate solution, and an alkaline amino acid solution is added while stirring to form a white suspension slurry, which is left for a period of time. The slurry is then transferred to a hydrothermal reactor, and a hydrothermal reaction is carried out for 5-20 hours under the conditions of 0.4-1.0mPa and 140-200°C. After the reaction is completed, it is cooled to room temperature, and the resulting product is filtered and washed 6 times with deionized water, with a water dosage of g / 10-20ml. Then it is vacuum dried at 100-120°C for 10-20 hours to obtain 152-type fibrous basic magnesium sulfate whiskers. Among them, the ratio (mol) of magnesium acetate to magnesium sulfate is 1.0:3.0-6.0. The pH regulator used is selected from the following amino acid monomers: Lysine,

[0057] Histidine, Arginine. The ratio of amino acid to magnesium sulfate is (mol) 1.0:1.0-2.0. Further, the obtained 152 type basic magnesium sulfate whisker is dehydrated and dried at 240-250° C. for 2-10 hours to obtain 150 type basic magnesium sulfate whisker.

[0058] In order to synthesize high molecular weight polylactide with suitable degradation cycle. According to the cycle of tissue trauma recovery, the polylactide provided is required to be mostly degraded within 4 months, that is, to reach more than 80%, so as to leave sufficient space and time for tissue repair and reconstruction. If the degradation is too slow, the material will hinder the repair and functional recovery of tissues in the body, and if the degradation is too fast, the purpose of ligation, fixation and isolation cannot be achieved. Therefore, under the premise of ensuring the molecular weight of polylactide, the present invention introduces glucono-δ-lactone Glucono-γ-lactone D-Mannos-1,4-lactone and L-mannose-1,4-lactone As a degradation rate regulating component. These sugar acid lactones have a lactone structure and multiple hydroxyl groups. They can be used as lactide polymerization initiating monomers, and can also enhance the polarity and hydrophilicity of polylactide, promote the surface interaction between polylactide and tissue fluid, and increase the degradation rate. After the selected sugar acid lactone is dried under high vacuum, it is polymerized together with the lactide monomer to obtain a high molecular weight polylactide with a suitable degradation cycle. Due to the introduction of sugar acid lactone, m in the above formula I 2 It can be expressed as: In formula II, A is lactide, m1 is the number of lactide monomers, m1≥8, B is saccharolactone, including glucono-δ-lactone, glucono-γ-lactone, D-mannose-1,4-lactone and L-mannose-1,4-lactone, and the molar fraction of saccharolactone is less than or equal to 20, that is, not more than 20 mol%, preferably 2.5-10.0 mol%.

[0059] Therefore, the above formula I can be expressed as

[0060] Furthermore, since tin ions have strong neurotoxicity, the present invention selects non-tin catalysts as polymerization catalysts. Since obtaining high molecular weight PLA requires an efficient catalyst, and commonly used tin compounds such as stannous octoate have strong toxicity and are difficult to separate from the polymer, the present invention requires a non-toxic, tissue-friendly catalyst.

[0061] Furthermore, the present invention selects tetrabutyl titanate Tetrabutyl zirconate Amino acid zinc catalysts such as zinc phenylalaninate, amino acid tin catalysts such as tin phenylalaninate, etc. are used as catalysts for the synthesis of polylactide. In order to reduce the amount of tin used, the present invention adopts a combined catalyst, and the above catalysts are used for polymerization catalysis according to a combination of two or more. Such as tetrabutyl titanate and zinc phenylalaninate combination, tetrabutyl titanate and tin phenylalaninate combination, tetrabutyl titanate, zinc phenylalaninate and tin phenylalaninate combination, etc., with the least or no tin element to achieve the synthesis of high molecular weight polylactide as the goal, and the catalyst can also catalyze the use of sugar acid lactone components to open the ring, and copolymerize with lactide to form high molecular weight polylactide. Titanate and amino acid zinc (amino acid tin) ratio is 1.0: 1.0-2.0 (wt). The amount of catalyst is 0.1-1.0wt% of the total amount of polymerization monomers. Among them, amino acid zinc and amino acid tin can be prepared as described in the present invention. Specifically, phenylalanine is added to a reactor with heating, stirring and nitrogen protection, and solvents such as water, methanol, ethanol, tetrahydrofuran, and dioxane are added, and the ratio of the total amount of amino acids to the solvent is 1 (mol): 1-2L; then guanidine carbonate is added, and the molar ratio of guanidine carbonate to amino acids is 0.5-1.0: 1; then the temperature is raised to 50-80°C under nitrogen protection, and a transparent solution is formed after about 30 minutes. Further, zinc chloride or zinc sulfate is configured into a water or methanol solution and added to the above solution, reacted with 50-80°C under nitrogen protection for 3-8 hours and then cooled to room temperature, and filtered to obtain a zinc complex of phenylalanine. After washing twice with methanol, ethanol, tetrahydrofuran or dioxane, it is dried in a vacuum oven at 60°C for 12-24 hours. When synthesizing amino acid tin, stannous chloride is used to replace zinc chloride or zinc sulfate. The ratio of zinc chloride or zinc sulfate (stannous chloride) to phenylalanine is (mol) 0.45-0.55: 1.0.

[0062] Furthermore, alcohols are generally used as initiators for lactide polymerization, such as benzyl alcohol, cyclohexyl sterol, etc. These initiators are highly effective in initiating ring-opening polymerization, but they are mixed in the polymer and need to be removed after the polymerization is completed, otherwise the polymer properties will be affected. However, the polymer is sensitive to water and cannot be washed with water. Using other solvents for washing increases both the process and the cost. Therefore, sugar acid lactone is selected as an initiator, which can be used as both an initiator and a polymerization monomer, increasing the hydrophilicity and polarity of the polymer. The degradation rate of the polymer in aqueous solutions such as blood, tissue fluid, etc. will be accelerated, and its toughness will also increase due to the presence of the comonomer.

[0063] Further, another key technology provided by the present invention is the polymerization process route of active sugar acid lactone lactide polymer. The polymerization reaction needs to be in a vacuum anhydrous and oxygen-free environment, and the polymer container needs to be dehydrated and deoxygenated. In the present invention, a reactor that can be continuously vacuumed can be used, and the reactor uses a ceramic liner. A reactor with a heated liner and a ceramic liner is used, and the reactor can have a high-purity nitrogen or argon interface outlet, a vacuum interface (T-interface, closed after the vacuum degree reaches the requirement, opened when needed), a thermocouple temperature display, online monitoring of the reaction temperature, and a magnetic stirrer that can be stirred in the liquid state to ensure the uniformity of material distribution of the liquid system. Specifically, before adding raw materials and catalysts, a reactor with a heated liner and a ceramic liner can be passed through high-purity nitrogen and heated to 120°C, and high-purity nitrogen is continuously passed at this temperature for 15 minutes. Further, the T-interface is closed and the nitrogen is stopped. The temperature is reduced to 30-50°C, and then lactide, sugar acid lactone, basic magnesium sulfate whisker, tetrabutyl titanate-phenylalanine zinc (tin) complex are added by opening the feed port, and then the feed port is closed. Reopen the nitrogen, open the T-interface, and pass nitrogen for 15 minutes; further, close the T-interface, turn off the nitrogen, start vacuuming, when the vacuum degree is less than 50Pa, close the T-interface, start heating, when the temperature reaches 120-150°C, stop heating, and start stirring, stop stirring after 20 minutes. Then react at 120-150°C for 2-6 hours, and then heat to 130-160°C for 5-15 hours.

[0064] Further, after the polymerization is completed, a non-protonic solvent is used to dissolve and purify the polymer, and the selected solvent is 1,2-dichloroethane, chloroform, dichloromethane, etc., and the amount thereof is 1g (polymer) / 5-10ml (solvent). After the polymerization is completed, when the polymer cools to room temperature, the solvent is injected into the reactor, and after it is completely dissolved, the polymer solution is discharged from the discharge port, and then a polar solvent such as methanol, ethanol, tetrahydrofuran, and dioxane is added to precipitate the polymer, and the solvent is washed 5-8 times and then placed in a high vacuum oven for drying, the drying temperature is 60-80°C, and the drying time is 6-18 hours, preferably 8-12 hours.

[0065] Further, after mixing the basic magnesium sulfate whisker and the synthesized polylactide, a twin-screw extruder is used to extrude in a molten state to form a polylactide composite reinforced by basic magnesium sulfate whiskers. Before extrusion, the synthesized polylactide and basic magnesium sulfate whiskers are fully dried in a vacuum oven, the extrusion feed hopper is dried with nitrogen, and the polylactide and basic magnesium sulfate whiskers are added to the feed hopper under nitrogen protection, and the discharge port of the twin-screw extruder is protected by nitrogen or dry ice to prevent the basic magnesium sulfate whisker polylactide composite from being oxidized or absorbing water by air. After the basic magnesium sulfate whisker reinforced polylactide composite strips are obtained at the discharge port and pelletized, they are sealed and stored. This process prepares a basic magnesium sulfate whisker polylactide composite covering 2.5wt%-20wt% basic magnesium sulfate whiskers.

[0066] Furthermore, the prepared magnesium sulfate whisker polylactide composite was processed into samples such as strips, films, and ligation clips for mechanical, degradation, and biological evaluations.

[0067] Furthermore, the dried polymer was micro-injected into mechanical specimens at 180-200° C. using a Haake rheometer.

[0068] Molecular weight test: The intrinsic viscosity is measured at 37±0.1℃, the formula is as follows: η=[2(η sp –lnηr)] 1 / 2 / C. C is the viscosity of the polymer solution (g / L); η r is the relative viscosity, dilute solution = t / t0; η sp is the specific viscosity, η sp =η r -1. η=KMα, calculate the viscosity average molecular weight of polylactide (where K=1.04×10-4, α=0.75); molecular weight distribution is tested by GPC, and the solvent is THF.

[0069] (1) Determination of molecular weight The molecular weight of polylactide (PLA) was determined by viscosity method. Accurately weigh a certain amount of product (about 0.080-0.1009), dissolve it in a 100mL volumetric flask with THF, and shake overnight. Use an Ubbelohde viscometer with a capillary diameter of 0.46mm in a 37.°C constant temperature water bath to measure its outflow time t, measure the outflow time to of the pure solvent, and use the one-point method to calculate the intrinsic viscosity of PLA. (2) Determination of molecular weight distribution The molecular weight distribution was carried out on a Water 410 gel chromatography analyzer, the solvent was THF, the mobile phase outflow rate was 1.00mL / min, and the temperature was 35°C.

[0070] Thermal performance test: The thermal performance test was performed using a DEC-7 differential scanning calorimeter (DSC) from Perkin-Elemer, USA, to determine the melting point (Tm) of the PLA product. The starting temperature was set at 20°C, the heating rate was 10°C / min, and the atmosphere was nitrogen.

[0071] Mechanical properties test: tensile strength and flexural modulus were measured according to GB13022-91 method.

[0072] Degradation test method: Take the injection molded material and perform degradation test in PBS solution: The preparation method of PBS is as follows; accurately weigh KH 2 PO 4 (0.544 g), Na 2 HPO 4 12H2O (7.16g), NaCl (16g) and KCl (0.402g) were dissolved in 2L deionized water, and the volume was fixed with a volumetric flask. The pH measurement range was between 7.2-7.4. The sample was placed in a centrifuge tube and a certain amount of PBS solution was added. The volume ratio of the PBS solution to the sample mass was 1g / 30mL. The centrifuge tube containing the sample was then placed in a constant temperature oscillating box at a temperature of 37°C and a speed of 80rpm / min. The sample was taken out and the solution was replaced on 1 (1D), 1w, 4w, and 12w days. The sample was rinsed with deionized water, vacuum dried, weighed, and the weight loss rate was calculated. The total weight loss rate for 12 weeks was used as the standard. Three control groups were set up for each sample.

[0073] pH determination: The supernatant of the sample was measured using a pH meter and PBS was replaced every 7 days.

[0074] Cytotoxicity and cell proliferation rate test: Prepare the extraction solution in accordance with the provisions of T16886 on biological materials, and calculate the proliferation rate by comparing the standard extract with the blank.

[0075] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0076] Embodiment 1:

[0077] (1) Preparation of basic magnesium sulfate whiskers: 246.5 g of magnesium sulfate heptahydrate (MgSO 4 7H 2 0) was added to 500 ml of deionized water and fully dissolved, and then 500 mL of deionized water was added and stirred to obtain a 1 L, 1 M magnesium sulfate solution. 155.4 g of magnesium acetate (C 4 H 6 O 4Mg) was added into 500ml deionized water and fully dissolved, then 500ml deionized water was added and stirred to obtain 1L, 1M magnesium acetate solution. 330.0g arginine was dissolved in 100ml deionized water and fully dissolved, then 100ml deionized water was added and stirred to obtain 2L, 1M arginine solution.

[0078] 200ml, 1M magnesium acetate solution was added to 1L, 1M magnesium sulfate solution, and 1.5L, 1M arginine solution was added while stirring to form a white suspension slurry, which was placed for 2 hours. The slurry was then transferred to a 10L stainless steel hydrothermal reactor, reacted at 0.6MPa, 150°C for 6 hours, heated to 0.9MPa, 190°C for 10 hours, cooled to room temperature after the reaction, and the product was filtered and washed 6 times with deionized water, with a water consumption of g product / 10-20ml. Then it was vacuum dried at 110°C for 12 hours to obtain 138g of fibrous 152-type basic magnesium sulfate whiskers.

[0079] (2) Catalyst preparation:

[0080] 1) Synthesis of arginine / L-phenylalanine zinc: Arginine (17.5 g, about 0.1 mol), L-phenylalanine (16.5 g, about 0.1 mol) and methanol (300 ml) were added to a 1L three-necked flask, stirred and reacted in a constant temperature water bath at 60°C for 20 min, guanidine carbonate (24 g, about 0.2 mol) was added, and 50 ml of deionized water was added until all dissolved, and then nitrogen was introduced into the solution for 10 min to remove the oxygen in the solution and the reaction bottle, and 100 ml of a solution of zinc chloride in methanol water (methanol / water = 80 ml / 20 ml) (13.6 g, about 0.1 mol) was added in a nitrogen-filled environment. After the addition was completed in 30 minutes, the mixture was reacted at 60°C for 5 hours, cooled to room temperature, filtered, and the precipitate was washed with ethanol 4 times. The product was dried in a vacuum oven at 60°C for 24 hours to obtain 38 g; the moisture content after drying was less than 0.01%;

[0081] 2) Tetrabutyl titanate was added to anhydrous magnesium sulfate baked at 500°C and dried.

[0082] (3) Preparation of polylactide polymer:

[0083] A 10L ceramic reactor with a heating liner was introduced with high-purity nitrogen and heated to 120°C. High-purity nitrogen was continuously introduced at this temperature for 15 minutes. Then the T-interface was closed and the nitrogen was stopped. The temperature dropped to 30°C, and then the feed port was opened to add dried L-lactide (702g), 45g D-mannose-1,4-lactone and arginine / L-phenylalanine zinc (2.5g) prepared in step (2) and 2.5g tetrabutyl titanate; then the feed port was closed. The nitrogen was turned on again, the T-interface was opened, and nitrogen was passed for 15 minutes; further, the T-interface was closed, the nitrogen was turned off, and vacuum was started. When the vacuum degree was less than 50Pa, the T-interface was closed, and the temperature was started to rise. When the temperature reached 130°C, the temperature was stopped, and stirring was started. The stirring was stopped after 20 minutes. Then the reaction was carried out at 130°C for 6 hours, and then the temperature was raised to 140°C for 12 hours. The vacuum degree of the entire polymerization process was less than 50Pa. Then the temperature was lowered to room temperature, and 6 L of chloroform was added. After complete dissolution, the polymer solution was transferred to a 25 L stainless steel barrel, and 12 L of methanol was added to precipitate the polymer. After filtering, the polymer was washed with ethanol 5 times and dried in a high vacuum oven at 80 ° C for 12 hours to obtain 738 g of product (polylactide).

[0084] (4) 5 g of the basic magnesium sulfate whisker prepared in step (1) and 195 g of the polylactide prepared in step (3) are mixed and extruded at 195° C. using a Haake micro twin-screw extruder to obtain a basic magnesium sulfate-polylactide composite; wherein the operating table is protected by nitrogen and the extrusion is completed in a nitrogen environment; and then the polylactide obtained in step (3) and the basic magnesium sulfate-polylactide composite obtained in step (4) are injection molded into stretching and bending strips using a Haake micro injection molding machine, respectively.

[0085] Product testing analysis

[0086] According to the method in a specific embodiment of the present invention, the product is subjected to the following tests:

[0087] (1) The diameter and length of magnesium sulfate whiskers were observed by SEM at a magnification of 200 times; (2) Polylactide molecular weight test (viscometry and GPC); (3) Melting point (℃) test (DSC); (3) Mechanical properties test of magnesium sulfate polylactide composite: tensile strength (MPa) and flexural modulus (MPa); (4) Degradation performance test (degradation cycle, percentage of degradation in 12 weeks; pH change); (5) Cytotoxicity test (0-5 levels), proliferation rate (%).

[0088] Test results:

[0089] (1) Diameter and length of basic magnesium sulfate whiskers: diameter 0.3-0.5 μm, length: 75-105 μm.

[0090] (2) The weight average molecular weight of polylactide is 21.5000 and the molecular weight distribution coefficient is 1.21

[0091] (3) Melting point (℃): 169

[0092] (4) Tensile strength (MPa): 39, flexural modulus (MPa): 1200

[0093] (5) 12w degradation percentage (wt%): 87; pH: 6.0-6.5

[0094] (6) Cytotoxicity: Grade 0, cell proliferation rate: 109%.

[0095] Example 2 (same as Example 1, except that the content of D-mannose-1,4-lactone is different from that of Example 1)

[0096] The other steps are the same as those in Example 1, except for step (3):

[0097] (3) A 10L ceramic reactor with a heating liner was introduced with high-purity nitrogen and heated to 120°C. High-purity nitrogen was continuously introduced at this temperature for 15 minutes. Then the T-interface was closed and the nitrogen was stopped. The temperature dropped to 30°C, and then the feed port was opened to add dried L-lactide (685g), D-mannose-1,4-lactone (89g) and arginine / L-phenylalanine zinc (2.5g) prepared in (2) and 2.5g of tetrabutyl titanate. Then the feed port was closed. The nitrogen was turned on again, the T-interface was opened, and nitrogen was introduced for 15 minutes; further, the T-interface was closed, the nitrogen was turned off, and vacuum was started. When the vacuum degree was less than 50Pa, the T-interface was closed, and the temperature was raised. When the temperature reached 130°C, the temperature was stopped, and stirring was started. The stirring was stopped after 20 minutes. Then the reaction was carried out at 130°C for 6 hours, and then the temperature was raised to 140°C for 12 hours. The vacuum degree of the whole polymerization process was less than 50Pa. Then the temperature was lowered to room temperature, and 6L of chloroform was added. After complete dissolution, the polymer solution was transferred to a 25L stainless steel barrel, and 12L of methanol was added to precipitate the polymer. After filtering, it was washed with ethanol 5 times and placed in a high vacuum oven at 80°C for 12 hours to obtain 739g of product.

[0098] Test results:

[0099] (1) Diameter and length of basic magnesium sulfate whiskers: diameter 0.3-0.5 μm, length: 75-105 μm.

[0100] (2) The weight average molecular weight of polylactide is 19.8000 and the molecular weight distribution coefficient is 1.33

[0101] (3) Melting point (℃): 168

[0102] (4) Tensile strength (MPa): 37, flexural modulus (MPa): 1100

[0103] (5) 12w degradation percentage (wt%): 88; pH: 6.0-6.5

[0104] (6) Cytotoxicity: Grade 0, cell proliferation rate: 109%.

[0105] Example 3 (same as Example 1, except that the polymerization catalysts used are tetrabutyl titanate and tin phenylalanine)

[0106] The other steps are the same as those in Example 1, except that step (2) synthesizing phenylalanine tin to replace arginine / L-phenylalanine zinc, and step (3) are different:

[0107] (3) Preparation of polylactide polymer: A 10L ceramic reactor with a heating liner was introduced with high-purity nitrogen and heated to 120°C. High-purity nitrogen was continuously introduced at this temperature for 15 minutes. Then the T-interface was closed and the nitrogen was stopped. The temperature dropped to 30°C, and then the feed port was opened to add dried L-lactide (702g), 45g D-mannose-1,4-lactone, L-phenylalanine tin (2.5g) prepared in (2) and 2.5g tetrabutyl titanate. Then the feed port was closed. The nitrogen was reopened, the T-interface was opened, and nitrogen was introduced for 15 minutes; further, the T-interface was closed, the nitrogen was turned off, and vacuum was started. When the vacuum degree was less than 50Pa, the T-interface was closed, and the temperature was started to rise. When the temperature reached 130°C, the temperature was stopped, and stirring was started. The stirring was stopped after 20 minutes. Then the reaction was carried out at 130°C for 6 hours, and then the temperature was raised to 140°C for 12 hours. The vacuum degree during the whole polymerization process was less than 50Pa. Then the temperature was lowered to room temperature, and 6L of chloroform was added. After complete dissolution, the polymer solution was transferred to a 25L stainless steel barrel, and 12L of methanol was added to precipitate the polymer. After filtering, it was washed with ethanol 5 times and placed in a high vacuum oven at 80°C for 12 hours to obtain 738g of product.

[0108] Test results:

[0109] (1) Diameter and length of basic magnesium sulfate whiskers: diameter 0.3-0.5 μm, length: 75-105 μm.

[0110] (2) The weight average molecular weight of polylactide is 29.6000 and the molecular weight distribution coefficient is 1.26

[0111] (3) Melting point (℃): 169

[0112] (4) Tensile strength (MPa): 45, flexural modulus (MPa): 1300

[0113] (5) 12w degradation percentage (wt%): 85; pH: 6.2-6.8

[0114] (6) Cytotoxicity: Grade 0, cell proliferation rate: 101%.

[0115] Example 4 (same as Example 1, except that glucono-γ-lactone was used instead of D-mannose-1,4-lactone)

[0116] Test results:

[0117] (1) Diameter and length of basic magnesium sulfate whiskers: diameter 0.3-0.5 μm, length: 75-105 μm.

[0118] (2) The weight average molecular weight of polylactide is 21.5000 and the molecular weight distribution coefficient is 1.21

[0119] (3) Melting point (℃): 169

[0120] (4) Tensile strength (MPa): 39, flexural modulus (MPa): 1200

[0121] (5) 12w degradation percentage (wt%): 87; pH: 6.0-6.5

[0122] (6) Cytotoxicity: Grade 0, cell proliferation rate: 111%.

[0123] Example 5 (same as Example 1, except that the basic magnesium sulfate whisker and lactide are polymerized together)

[0124] (1)-(2) Same as Example 1.

[0125] (3) Preparation of composite by copolymerization of magnesium sulfate whisker and polylactide. A 10L ceramic reactor with a heating liner was introduced with high-purity nitrogen and heated to 120°C. High-purity nitrogen was continuously introduced at this temperature for 15 minutes. Then the T-interface was closed and the nitrogen was stopped. The temperature dropped to 30°C, and then the feed port was opened to add dried L-lactide (702g), 45g D-mannose-1,4-lactone and arginine / L-phenylalanine zinc (2.5g) prepared in (2), and 2.5g tetrabutyl titanate. Finally, 20.0g of basic magnesium sulfate whisker prepared in (1) was added, and then the feed port was closed. The nitrogen was turned on again, the T-interface was opened, and nitrogen was introduced for 15 minutes; further, the T-interface was closed, the nitrogen was turned off, and vacuum was started. When the vacuum degree was less than 50Pa, the T-interface was closed, and the temperature was started to rise. When the temperature reached 130°C, the temperature was stopped and stirring was started. The stirring was stopped after 20 minutes. Then react at 130°C for 6 hours, then heat to 140°C for 12 hours. The vacuum degree of the entire polymerization process is less than 50Pa. Then cool to room temperature, and then add 6L of chloroform. After complete dissolution, transfer the polymer solution to a 25L stainless steel barrel, add 12L of methanol to precipitate the polymer, filter, wash with ethanol 5 times, and place in a high vacuum oven at 80°C to dry for 12 hours to obtain 758g of product.

[0126] (4)-(5) Same as Example 1

[0127] Test results:

[0128] (1) Diameter and length of basic magnesium sulfate whiskers: diameter 0.3-0.5 μm, length: 75-105 μm.

[0129] (2) Composite melt index (200°C, g / 10min): 52

[0130] (3) Melting point (℃): 169

[0131] (4) Tensile strength (MPa): 39, flexural modulus (MPa): 1200

[0132] (5) 12w degradation percentage (wt%): 91; pH: 6.3-6.8

[0133] (6) Cytotoxicity: Grade 0, cell proliferation rate: 112%.

[0134] Example 6 (same as Example 1, except that the basic magnesium sulfate whisker content is increased to 7.5%)

[0135] The other steps are the same as those in Example 1, except for step (4):

[0136] (4) 15 g of the obtained magnesium sulfate whisker and 185 g of the polylactide prepared in step (3) were mixed and extruded at 190° C. through a Hake micro twin-screw extruder. The operating table was protected by nitrogen. After the extrusion was completed in a nitrogen environment, the polylactide and magnesium sulfate polylactide composite obtained in (3) and (4) was injection molded into stretched and bent strips using a Hake micro injection molding machine.

[0137] Test results:

[0138] (1) Diameter and length of basic magnesium sulfate whiskers: diameter 0.3-0.5 μm, length: 75-105 μm.

[0139] (2) The weight average molecular weight of polylactide is 21.5000 and the molecular weight distribution coefficient is 1.21

[0140] (3) Melting point (℃): 169

[0141] (4) Tensile strength (MPa): 45, flexural modulus (MPa): 1500

[0142] (5) 12w degradation percentage (wt%): 82; pH: 7.0-7.1

[0143] (6) Cytotoxicity: Grade 0, cell proliferation rate: 115%.

[0144] Example 7 (same as Example 1, except that the basic magnesium sulfate whisker content is increased to 10.0%)

[0145] (1)-(3) are the same as in Example 1.

[0146] 20 g of the basic magnesium sulfate whiskers prepared by (4) and 180 g of the polylactide prepared by (3) were mixed and extruded at 190° C. through a Hake micro twin-screw extruder. The operating table was protected by nitrogen. After the extrusion was completed in a nitrogen environment, the polylactide and basic magnesium sulfate polylactide composite obtained by (3) and (4) were injection molded into stretching and bending strips using a Hake micro injection molding machine.

[0147] Test results:

[0148] (1) Diameter and length of basic magnesium sulfate whiskers: diameter 0.3-0.5 μm, length: 75-105 μm.

[0149] (2) The weight average molecular weight of polylactide is 21.5000 and the molecular weight distribution coefficient is 1.21

[0150] (3) Melting point (℃): 170

[0151] (4) Tensile strength (MPa): 49, flexural modulus (MPa): 1700

[0152] (5) 12w degradation percentage (wt%): 83; pH: 7.1-7.2

[0153] (6) Cytotoxicity: Grade 0, cell proliferation rate: 112%.

[0154] Example 8 (same as Example 1, except that the basic magnesium sulfate whisker content is increased to 15%)

[0155] (1)-(3) are the same as in Example 1.

[0156] 30 g of the basic magnesium sulfate whiskers prepared by (4) and 170 g of the polylactide prepared by (3) were mixed and extruded at 190° C. through a Hake micro twin-screw extruder. The operating table was protected by nitrogen. After the extrusion was completed in a nitrogen environment, the polylactide and basic magnesium sulfate polylactide composite obtained by (3) and (4) were injection molded into stretching and bending strips using a Hake micro injection molding machine.

[0157] Test results:

[0158] (1) Diameter and length of basic magnesium sulfate whiskers: diameter 0.3-0.5 μm, length: 75-105 μm.

[0159] (2) The weight average molecular weight of polylactide is 21.5000 and the molecular weight distribution coefficient is 1.21

[0160] (3) Melting point (℃): 169

[0161] (4) Tensile strength (MPa): 50, flexural modulus (MPa): 1900

[0162] (5) 12w degradation percentage (wt%): 81; pH: 7.1-7.3

[0163] (6) Cytotoxicity: Grade 0, cell proliferation rate: 113%.

[0164] Example 9 (same as Example 1, except that the basic magnesium sulfate whisker content is increased to 20.0%)

[0165] (1)-(3) are the same as in Example 1.

[0166] 40 g of the basic magnesium sulfate whiskers prepared by (4) and 160 g of the polylactide prepared by (3) were mixed and extruded at 190° C. through a Haake micro twin-screw extruder. The operating table was protected by nitrogen. After the extrusion was completed in a nitrogen environment, the polylactide and basic magnesium sulfate polylactide composite obtained by (3) and (4) were injection molded into stretching and bending strips using a Haake micro injection molding machine.

[0167] Test results:

[0168] (1) Diameter and length of basic magnesium sulfate whiskers: diameter 0.3-0.5 μm, length: 75-105 μm.

[0169] (2) The weight average molecular weight of polylactide is 21.5000 and the molecular weight distribution coefficient is 1.21

[0170] (3) Melting point (℃): 169

[0171] (4) Tensile strength (MPa): 55, flexural modulus (MPa): 2100

[0172] (5) 12w degradation percentage (wt%): 81; pH: 7.0-7.3

[0173] (6) Cytotoxicity: Grade 0, cell proliferation rate: 117%.

[0174] Example 10 (same as Example 1, except that type 150 basic magnesium sulfate whiskers are used instead of type 152)

[0175] (1) Preparation of basic magnesium sulfate whiskers: 246.5 g of magnesium sulfate heptahydrate (MgSO 4 7H 2 1L, 1M magnesium sulfate solution.2) join in 500ml deionized water, fully dissolve, then add 500mL deionized water, stir, and obtain the magnesium sulfate solution of 1L, 1M.155.4g magnesium acetate (C4H6O4Mg) join in 500ml deionized water, fully dissolve, then add 500mL deionized water, stir, and obtain the magnesium acetate solution of 1L, 1M.330.0g arginine is dissolved in 100ml deionized water, fully dissolve, then add 100mL deionized water, stir, and obtain the arginine solution of 2L, 1M.200ml, 1M magnesium acetate solution solution joins in 1L, 1M magnesium sulfate solution, adds 1.5L, 1M arginine solution while stirring, forms white suspension slurry, places 2 hours. The slurry was then transferred to a 10L stainless steel hydrothermal reactor, reacted at 0.6MPa and 150°C for 6 hours, heated to 0.9MPa and 190°C for 10 hours, cooled to room temperature after the reaction, and the product was filtered and washed 6 times with deionized water, with the amount of water being g / 10-20ml. Then it was vacuum dried at 110°C for 12 hours to obtain 138g of fibrous 152-type basic magnesium sulfate whiskers.

[0176] The obtained 152 type basic magnesium sulfate whiskers were dried at 260° C. under vacuum for 12 hours to remove crystal water.

[0177] (2)-(5) are the same as in Example 1.

[0178] Test results:

[0179] (1) Diameter and length of basic magnesium sulfate whiskers: diameter 0.5-0.8 μm, length: 80-110 μm.

[0180] (2) The weight average molecular weight of polylactide is 21.5000 and the molecular weight distribution coefficient is 1.21

[0181] (3) Melting point (℃): 169

[0182] (4) Tensile strength (MPa): 409, flexural modulus (MPa): 1300

[0183] (5) 12w degradation percentage (wt%): 87; pH: 6.3-6.6

[0184] (6) Cytotoxicity: grade 0, cell proliferation rate: 110%.

[0185] Comparative Example 1: Synthesis and Performance of Traditional PLA

[0186] A 10L reactor with a ceramic heating liner was introduced with high-purity nitrogen and heated to 120°C. High-purity nitrogen was continuously passed at this temperature for 15 minutes. Then the T-interface was closed and the nitrogen was stopped. The temperature dropped to 50°C, and then the dried L-lactide (1000g) and 5g of stannous octoate were added by opening the feed port. Then the feed port was closed. The nitrogen was reopened, the T-interface was opened, and nitrogen was passed for 15 minutes; further, the T-interface was closed, the nitrogen was turned off, and vacuum was started. When the vacuum degree was less than 50Pa, the T-interface was closed, and the temperature was started to rise. When the temperature reached 130°C, the temperature was stopped, and stirring was started. The stirring was stopped after 20 minutes. Then the reaction was carried out at 130°C for 6 hours, and then the temperature was raised to 140°C for 12 hours. The vacuum degree of the entire polymerization process was less than 50Pa. Then the temperature dropped to room temperature, and then 6L of chloroform was added. After complete dissolution, the polymer solution was transferred to a 25 L stainless steel barrel, and 12 L of methanol was added to precipitate the polymer. After filtering, it was washed with ethanol 5 times and placed in a high vacuum oven at 80°C for 12 hours to obtain 829 g of product.

[0187] The test was the same as in Example 1.

[0188] Test results:

[0189] (1) The weight average molecular weight is 55.3000 and the molecular weight distribution coefficient is 1.32

[0190] (2) Melting point (℃): 175

[0191] (3) Tensile strength (MPa): 50 and elongation at break (%) 4.5; flexural modulus 231 MPa

[0192] (4) Degradation cycle (w): 60; pH: 2.5-4.5

[0193] (5) Cytotoxicity: Grade 1, cell proliferation rate: 65%.

[0194] It has high molecular weight and high strength, but poor toughness, low modulus and poor rigidity; the degradation cycle is long and the pH is low during the degradation process, which is not conducive to tissue growth.

[0195] Comparative Example 2: The same as Example 1, except that basic magnesium sulfate whiskers were not added, but d-mannonic acid 1-4-lactone was added.

[0196] Test results:

[0197] (1) The weight average molecular weight of polylactide is 21.5000 and the molecular weight distribution coefficient is 1.21

[0198] (2) Melting point (℃): 169

[0199] (3) Tensile strength (MPa): 40, flexural modulus (MPa): 182

[0200] (4) 12w degradation percentage (wt%): 87; pH: 2.3-4.6

[0201] (5) Cytotoxicity: Grade 1, cell proliferation rate: 65%.

[0202] The toughness is poor and the pH is low during the degradation process, which is not conducive to tissue growth.

[0203] Comparative Example 3: Same as Example 1, except that basic magnesium sulfate whiskers were added and d-mannonic acid 1-4 lactone was removed during the polymerization process. Test results:

[0204] (1) Diameter and length of basic magnesium sulfate whiskers: diameter 0.3-0.5 μm, length: 75-105 μm.

[0205] (2) The weight average molecular weight of polylactide is 23.3000 and the molecular weight distribution coefficient is 1.25

[0206] (3) Melting point (℃): 171

[0207] (4) Tensile strength (MPa): 43, flexural modulus (MPa): 1300

[0208] (5) 12w degradation percentage (wt%): 65; pH: 6.0-6.5

[0209] (6) Cytotoxicity: Grade 0, cell proliferation rate: 111%.

[0210] Compared with Example 1, the degradation is slow and the degradation period is long, which does not match the tissue repair recovery period.

[0211] Compared with Example 1, the degradation is slowed down, the degradation period is prolonged, and the toughness is reduced.

[0212] Comparative Example 4: Same as Example 1, except that only tetrabutyl titanate was used as the catalyst and zinc phenylalanine was removed.

[0213] Test results:

[0214] (1) Diameter and length of basic magnesium sulfate whiskers: diameter 0.3-0.5 μm, length: 75-105 μm.

[0215] (2) The weight average molecular weight of polylactide is 12.6000 and the molecular weight distribution coefficient is 1.39

[0216] (3) Melting point (℃): 169

[0217] (4) Tensile strength (MPa): 35, flexural modulus (MPa): 900

[0218] (5) 12w degradation percentage (wt%): 93; pH: 6.0-6.5

[0219] (6) Cytotoxicity: grade 0, cell proliferation rate: 105%.

[0220] Compared with Example 1, the copolymer has a low molecular weight, rapid degradation, and low tensile strength and flexural modulus.

[0221] Comparative Example 5: Same as Example 1, except that only zinc phenylalanine was used as the catalyst and tetrabutyl titanate was removed.

[0222] Test results:

[0223] (1) Diameter and length of basic magnesium sulfate whiskers: diameter 0.3-0.5 μm, length: 75-105 μm.

[0224] (2) The weight average molecular weight of polylactide is 11.3000 and the molecular weight distribution coefficient is 1.41

[0225] (3) Melting point (℃): 167

[0226] (4) Tensile strength (MPa): 33, flexural modulus (MPa): 830

[0227] (5) 12w degradation percentage (wt%): 95; pH: 6.0-6.5

[0228] (6) Cytotoxicity: Level 0, cell proliferation rate: 102%.

[0229] Compared with Example 1, the copolymer has a low molecular weight, rapid degradation, and low tensile strength and flexural modulus.

[0230] Comparative Example 6: Same as Example 1, except that stannous octoate was used as a catalyst to replace the combined catalyst of Example 1. Test results:

[0231] (1) Diameter and length of basic magnesium sulfate whiskers: diameter 0.3-0.5 μm, length: 75-105 μm.

[0232] (2) The weight average molecular weight of polylactide is 60.1000 and the molecular weight distribution coefficient is 1.28

[0233] (3) Melting point (℃): 173

[0234] (4) Tensile strength (MPa): 55, flexural modulus (MPa): 1.3

[0235] (5) 12w degradation percentage (wt%): 82; pH: 6.0-6.5

[0236] (6) Cytotoxicity: Grade 1, cell proliferation rate: 68%.

[0237] Stannous octoate has high catalytic performance and can obtain higher molecular weight aggregates, but tin catalysts are more toxic to cells than zinc catalysts, and further washing and replacement of residual tin in polylactide are required.

[0238] It should be noted that the specification of the present invention provides the preferred embodiments of the present invention, but the present invention can be implemented in many different forms and is not limited to the embodiments described in this specification. These embodiments are not intended to be additional limitations on the content of the present invention. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. In addition, the above-mentioned technical features continue to be combined with each other to form various embodiments not listed above, which are all considered to be within the scope of the present invention specification; further, for ordinary technicians in this field, they can be improved or transformed according to the above description, and all these improvements and transformations should belong to the protection scope of the claims attached to the present invention.

Claims

1. A polylactide composite reinforced with basic magnesium sulfate whiskers, characterized in that: The polylactide composite comprises the following components in mass fractions: 80-97.5% of polylactide modified by saccharolactone and 2.5-20% of basic magnesium sulfate whisker.

2. The polylactide compound according to claim 1, characterized in that: The polylactide modified by saccharolactone is prepared by copolymerization of lactide and saccharolactone, wherein the content of lactide is 80-99 mol % and the content of saccharolactone is 1-20 mol %.

3. The polylactide compound according to claim 1 or 2, characterized in that: The saccharolactone includes at least one of glucono-δ-lactone, glucono-γ-lactone, D-mannose-1,4-lactone and L-mannose-1,4-lactone.

4. The polylactide compound according to claim 1, characterized in that: The basic magnesium sulfate whisker is at least one of type 152 and type 150 basic magnesium sulfate whiskers.

5. A method for preparing a polylactide composite reinforced with basic magnesium sulfate whiskers according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Preparation of basic magnesium sulfate whiskers: mixing an aqueous solution of a weakly alkaline organic magnesium salt with an aqueous solution of magnesium sulfate, then adding an aqueous solution of a basic amino acid under stirring, subjecting the uniformly mixed solution to a hydrothermal reaction, filtering and collecting the obtained reaction product, and washing and drying to obtain basic magnesium sulfate whiskers; (2) Preparation of polylactide modified with saccharo lactone: adding lactide, saccharo lactone and a catalyst into a reaction kettle under the protection of nitrogen or an inert gas, and reacting at 120-180° C. for 6-50 hours to obtain polylactide modified with saccharo lactone; (3) Preparation of a polylactide composite reinforced with basic magnesium sulfate whiskers: The basic magnesium sulfate whiskers prepared in step (1) and the polylactide modified with saccharolactone prepared in step (2) are melt-extruded together in a desired mass ratio to obtain a polylactide composite reinforced with basic magnesium sulfate whiskers.

6. The preparation method according to claim 5, characterized in that: The molar ratio of the weakly alkaline organic magnesium salt to magnesium sulfate is 1.0:3.0-6.0; Further, the molar ratio of the basic amino acid to magnesium sulfate is 1.0:1.0-2.0; Further, the organic magnesium salt with weak alkalinity includes at least one of magnesium acetate, magnesium propionate and magnesium butyrate; Further, the basic amino acid includes at least one of lysine, histidine and arginine; Further, the hydrothermal reaction is carried out under the conditions of 0.4-1.0 mPa and 140-200°C; Furthermore, the basic magnesium sulfate whisker is a 152 type basic magnesium sulfate whisker; Furthermore, the 152 type basic magnesium sulfate whisker is dried at 240-250° C. for 2-10 hours to obtain the 150 type basic magnesium sulfate whisker.

7. The preparation method according to claim 5, characterized in that: The catalyst comprises amino acid zinc and / or tin and titanate; Further, the amino acid in the amino acid zinc and / or tin includes at least one of phenylalanine, arginine, lysine and histidine; Furthermore, the amino acid zinc and / or tin is prepared as follows: amino acid zinc or tin complex is prepared using amino acid and zinc salt or tin salt as raw materials; Further, the zinc salt is zinc chloride or zinc sulfate, and the tin salt is stannous chloride; Further, the amino acid zinc and / or tin is prepared as follows: under the protection of nitrogen or inert gas, the amino acid is reacted with an inorganic guanidine salt in a solvent at 50-80° C. to generate an organic guanidine salt of phenylalanine, and then a water and / or alcohol solution of a zinc salt and / or tin salt is added, and the reaction is carried out at 50-80° C. for 3-8 hours to obtain a zinc and / or tin complex of the amino acid; Further, the ratio of the total amount of amino acid to the solvent is 1 (mol): 1-2 (L); Further, the molar ratio of amino acid to inorganic guanidine salt is 1:0.5-1.2; Further, the molar ratio of the amino acid to the zinc salt and / or tin salt is 2:1; Furthermore, the solvent is at least one of water, methanol, ethanol, tetrahydrofuran, and dioxane; Further, the inorganic guanidine salt is guanidine carbonate; Furthermore, the method further comprises filtering, collecting, washing and drying the obtained amino acid zinc and / or tin complex; Furthermore, the titanate includes at least one of tetrabutyl titanate and tetrabutyl zirconate.

8. The preparation method according to claim 5, characterized in that: The step (2) is carried out in an anhydrous and oxygen-free environment; Furthermore, before the heating reaction in step (2), the reaction kettle is evacuated; Furthermore, the reaction in step (2) is preferably carried out at 130-140° C., and the reaction time is preferably 16-32 hours; Further, the reaction includes reacting at 120-150° C. for 2-4 hours, then heating to 130-160° C. for 5-15 hours; Furthermore, step (2) further comprises adding a non-protonic solvent to the reactor to dissolve the harvested aminolactam and lactide polymer modified with saccharide lactone, and then precipitating and washing the polymer with a polar solvent and drying it.

9. The preparation method according to claim 5, characterized in that: In step (3), the melt extrusion is carried out under the protection of nitrogen or inert gas, and the discharge port of the melt extrusion is protected by nitrogen or dry ice to prevent the polylactide composite reinforced with basic magnesium sulfate whiskers from being oxidized by air or absorbing water.

10. Use of a polylactide composite reinforced with basic magnesium sulfate whiskers according to any one of claims 1 to 4 or prepared by the preparation method according to any one of claims 5 to 9 in medical treatment; Furthermore, the application includes application in soft tissue repair.

Citation Information

Patent Citations

  • Whisker reinforced biodegradable polyester composite material and preparation method

    CN105462193A

  • Method for preparing magnesium sulfate by catalyzing alkylated waste sulfuric acid through lignocellulose ester

    CN105502444A

  • Controllable biodegradable copolymer with alkaline copolymerization center

    CN109776778A

  • Biodegradable injection filler microsphere as well as preparation method and application thereof

    CN114225104A

  • Copolymer material and application thereof

    CN115591027A